Modal shift to inland waterway transport: Five case studies in the North Sea Region - Santén, Vendela; Rogerson, Sara; Williamsson, Jon; Woxenius, Johan (European Journal of Transport and Infrastructure Research, 2021)
Modal shift from road to water is a strategy prioritised by both the European Union and many of its member states. However, inland waterways remain underutilised in most member states, and even the small number of countries in which inland waterway transport is well established, the sector faces fierce competition from road-based solutions. There is potential to develop tools and strategies for expanding the use of inland waterways by better understanding what activities key actors can rely on to facilitate modal shift. In this multiple-case study, we identify activities that actors perform to realise modal shift to inland waterways in five cases from the North Sea Region, by conducting interviews, workshops, and field observations. In each case, the process of modal shift varied depending upon which actor initiated specific activities, the order of performing activities and the number of iterations required to advance. Activities revolved around understanding the current situation, identifying potential solutions, testing solutions and promoting solutions. Getting stakeholders on board and identifying goods flows were integrated in all themes. The structured and emergent approach were outlined, highlighting varying starting points (mature or immature market) and actor engagement (facilitating or initiating roles). Different actors could assume leading roles. Authorities can target initiatives and policies to form relevant alliances and support modal shift by approach, while practitioners can relate and be inspired by the described activities in the varying contexts and adhere to entrepreneurial roles. Realising large-scale modal shift requires multi-actor engagement, openness to emergent solutions and long-term endurance.